Dressing SMART For Boys - Jill Lowe
Dressing Smart for Boys provides smart, practical and cost-effective dressing strategies for teenage boys grappling with dressing issues in an image-conscious society. Designed for young teenage boys, the book comes in a visually-appealing and colourful format that is underpinned by a magazine-style design. With this book, teenage boys gain skills for dressing that will help them take charge of their image. make informed choices on dressing for their specific skin tone, body shape and for different occasions/events/functions. become empowered and confident individuals. give a positive impression of themselves to people they meet with their dressing.